El Quartelejo Pueblo Ruins, Scott County, Kansas - Shearmire, Brantlee (Kansas State University, The Chapman Center for Rural Studies, 2010)
In this paper, the author discusses the El Quartelejo Pueblo ruins located in present-day Scott County, Kansas. The Taos and the Picuris Indians who came from what is today northwestern New Mexico fled their homelands due to their Spanish overlords who denounced and prohibited the Indians from practicing their religious ceremonies, imposed Christianity upon them, and forced them into labor. Eventually the Spaniards sent a party of soldiers to retrieve the Indians and escort them back. The pueblo the Indians built would lie dormant for nearly 200 years before being discovered again, accidentally, by an early Scott County pioneer, Herbert Steele.
Shearmire, Brantlee, “El Quartelejo Pueblo Ruins, Scott County, Kansas,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/2.
Keywords: Archaeology; Brantlee Shearmire; El Quartelejo Pueblo; Herbert Steele; Pueblo Indians; Scott County